Pengaruh Work Place Spirituality, Person Job Fit, dan Leadership Style terhadap Intention to Stay Perawat Rumah Sakit PKU Muhammadiyah Sruweng - Much. Riyadus Solichin (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2019)
The purpose of this study was to examine the role of workplace spirituality, person job fit, and leadership style in the intention to stay nurses. This study involved 37 nurses at Muhammadiyah Hospital in Sruweng with non-permanent status as respondents who were taken using population sample techniques. Multiple regression analysis is used to test how the influence of each independent variable on the dependent variable. Data that has been collected is processed with the help of SPPS for Windows Series 24.0 statistical tools. The results showed that all hypotheses were accepted, meaning that workplace spirituality variables, person job fit, and leadership styles can have a significant influence on the intention to stay nurses. The findings from this study prove that workplace spirituality has the greatest influence on intention to stay, while person job fit has the lowest influence.